A negative electrode active material and preparation method thereof, negative electrode sheet and secondary battery
By using the negative electrode active material prepared by mixing chitosan and sodium alginate in sodium ion batteries, the uneven deposition and safety problems caused by too low sodium ion embedding points are solved, and the formation and magnification of multi-level pore structures are achieved. Performance improvement.
Patent Information
- Application Number
- CN202211189326.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-28
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2042-09-28
AI Technical Summary
The existing carbon materials in sodium ion batteries have too low embedding point, which leads to uneven deposition of sodium ions, dendrite growth, and short circuits caused by puncture of the diaphragm, which has problems with room for improvement in safety and rate performance.
The mixed gel was prepared by mixing chitosan and sodium alginate, and lyophilized by metal salt solution, followed by carbonization and acid washing to remove metal elements, and negative electrode active material with multi-layer pore structure was prepared.
This method effectively improves the pore structure of the negative electrode active material, reduces the ion conductivity, improves the rate performance, and accurately regulates the pore structure by controlling the heating rate of the carbonization process and the types of metal salt solutions, and enhances the electrolyte and its electrolyte metals Ion migration ability.
Smart Images

Figure CN117819515B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of battery materials, and in particular relates to a negative electrode active material and a preparation method thereof, a negative electrode sheet and a secondary battery. Background Art
[0002] As the negative electrode material of sodium ion batteries, carbon materials all face a problem, that is, the embedding point of sodium ions is too low. During high-rate charge and discharge, sodium ions easily form uneven deposition on the negative electrode surface, leading to the growth of dendrites, which will eventually pierce the diaphragm and cause a short circuit, resulting in safety problems. Therefore, there is a lot of room for improvement in the rate performance of sodium ion batteries.
[0003] In order to improve the rate performance of carbon materials, increasing the pore structure to increase the contact area with the electrolyte is an effective strategy. The general method uses an activation agent to mix with the carbon material, and uses the interaction between the two under high temperature conditions to produce a pore structure. However, this method will increase costs and environmental problems due to the introduction of the activation agent; in addition, the porous carbon material prepared in this way is mainly micropores, and the pore structure is too complex, which will increase the diffusion resistance of the electrolyte, and the specific surface area cannot be fully utilized. Summary of the invention
[0004] In view of the problem that existing carbon materials have insufficient electrolyte diffusion efficiency, the present invention provides a negative electrode active material and a preparation method thereof, a negative electrode sheet and a secondary battery.
[0005] The technical solution adopted by the present invention to solve the above technical problems is as follows:
[0006] In one aspect, the present invention provides a method for preparing a negative electrode active material, comprising the following steps:
[0007] The mixed gel is prepared by mixing chitosan and sodium alginate;
[0008] freeze-drying the mixed gel to obtain a precursor material;
[0009] The freeze-dried precursor material is infiltrated with a metal salt solution, wherein the metal salt solution is a metal salt solution with a valence greater than or equal to +2, dried and carbonized at a carbonization heating rate of 10 to 20°C / min to obtain a carbonized material;
[0010] The carbonized material is pickled with an acid solution to remove metal elements to obtain a negative electrode active material.
[0011] Optionally, the “mixing chitosan and sodium alginate to prepare a mixed gel” includes:
[0012] Chitosan is dispersed at a mass concentration of 0.5% to 3.5% to obtain a first gel solution, sodium alginate is dispersed at a mass concentration of 0.5% to 3.5% to obtain a second gel solution, and the first gel solution and the second gel solution are mixed at a mass ratio of 1: (0.5 to 2) to obtain a mixed gel.
[0013] Optionally, the freeze-drying treatment temperature is -10°C to -40°C, and the treatment time is 24 to 48 hours.
[0014] Optionally, the metal salt solution includes Fe 2+ 、Co 2+ 、Ni 2+ 、Zn 2+ , Cu 2+ , Ca 2+ or Fe 3+ One or more metal ions.
[0015] Optionally, the mass concentration of the metal salt in the metal salt solution is 1% to 3%, and during the treatment, the freeze-dried precursor material is immersed in the metal salt solution for 8 to 24 hours.
[0016] Optionally, in the "drying and carbonization treatment", the drying method is freeze-drying, the treatment temperature is -10°C to -40°C, the treatment time is 24 to 48 hours, the carbonization temperature is 800 to 1000°C, and the carbonization time is 3 to 5 hours.
[0017] Optionally, before the pickling operation, the carbonized material is ground into a granular carbonized material with an average particle size of 3 to 10 μm.
[0018] Optionally, after the pickling operation, water washing and vacuum drying are performed.
[0019] In another aspect, the present invention provides a negative electrode active material prepared by the preparation method described above.
[0020] Optionally, the negative electrode active material includes a porous carbon material, which includes macropores with a pore size greater than 200 nm, channels with an inner diameter of 20 to 70 nm, mesopores with a pore size of 2 to 50 nm, and micropores with a pore size less than 2 nm. The macropores are distributed inside and on the surface of the porous carbon material, the channels penetrate and connect different macropores, and the mesopores and the micropores are formed on the pore walls of the macropores and the inner walls of the channels.
[0021] Optionally, the porous carbon material is a hard carbon material.
[0022] Optionally, the negative electrode active material is in a granular form, and the average particle size of the negative electrode active material is 3 to 10 μm.
[0023] Optionally, the specific surface area of the negative electrode active material is 800 to 2500 m 2 / g.
[0024] Optionally, the reversible capacity of the negative electrode active material under 0.1C charge and discharge conditions is 310 to 400 mAh / g.
[0025] Optionally, the porous carbon material is doped with nitrogen, and the nitrogen is distributed inside the porous carbon material.
[0026] Optionally, based on the total mass of the porous carbon material being 100%, the doping amount of the nitrogen element is 2.6% to 5.2%.
[0027] In another aspect, the present invention provides a negative electrode sheet, comprising a negative electrode current collector and a negative electrode material layer covering the negative electrode current collector, wherein the negative electrode material layer comprises the negative electrode active material prepared by the preparation method described above or the negative electrode active material described above.
[0028] In another aspect, the present invention provides a secondary battery comprising the negative electrode sheet as described above.
[0029] Optionally, the secondary battery is a sodium ion battery.
[0030] According to the preparation method of the negative electrode active material provided by the present invention, sodium alginate and chitosan are used to prepare a mixed gel, in which the sodium alginate gel particles and the chitosan gel particles are combined with each other due to electrostatic adsorption to form a loose and porous mixed gel morphology, and the solvent in the mixed gel is filled in its pores. At this time, through freeze drying, on the one hand, the solvent in the pores can be removed, and on the other hand, the porous morphology of the mixed gel can be maintained to avoid the shrinkage of the mixed gel during the drying process, resulting in the collapse of the pores, and a framework mainly composed of macropores is obtained. At the same time, the precursor material after freeze drying is infiltrated with a metal salt solution, and the chelation between sodium alginate and metal ions can be used to fix the metal ions on the surface of the macropores. During the carbonization process, a large amount of gas escapes from the mixed gel of sodium alginate and chitosan, generating channels connecting multiple macropores, and at the same time, the gas escapes through the surface of the macropores and the channels, obtaining mesopores distributed on the surface of the macropores and the channels, and then the carbonized metal ions are removed by acid washing, leaving micropores with uniform distribution and smaller size. By controlling the heating rate of the carbonization process and the type of metal salt solution used, the pore structure of the negative electrode active material can be accurately and effectively regulated to obtain a more unobstructed multi-level pore structure that is conducive to the migration of the electrolyte and its electrolyte metal ions, which is beneficial to reducing the ionic conductivity of the negative electrode active material and improving the rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is an electron microscope photograph of the negative electrode active material provided by the present invention. DETAILED DESCRIPTION
[0032] In order to make the technical problems, technical solutions and beneficial effects solved by the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0033] One embodiment of the present invention provides a method for preparing the negative electrode active material as described above, comprising the following steps:
[0034] The mixed gel is prepared by mixing chitosan and sodium alginate;
[0035] freeze-drying the mixed gel to obtain a precursor material;
[0036] The freeze-dried precursor material is infiltrated with a metal salt solution, wherein the metal salt solution is a metal salt solution with a valence greater than or equal to +2, dried and carbonized at a carbonization heating rate of 10 to 20°C / min to obtain a carbonized material;
[0037] The carbonized material is pickled with an acid solution to remove metal elements to obtain a negative electrode active material.
[0038] It should be noted that the simultaneous addition of chitosan and sodium alginate to form a mixed gel and the freeze-drying operation of the mixed gel are necessary to form the multi-level pore structure with the above-mentioned specific distribution.
[0039] The term "freeze drying" refers to a method in which the mixed gel is first frozen to form a solid, and then the solvent therein is sublimated by reducing the pressure to achieve low-temperature drying.
[0040] In the mixed gel, the sodium alginate gel particles and the chitosan gel particles are combined with each other due to electrostatic adsorption to form a loose and porous mixed gel morphology, and the solvent in the mixed gel is filled in its pores. At this time, through freeze drying, on the one hand, the solvent in the pores can be removed, and on the other hand, the porous morphology of the mixed gel can be maintained, avoiding the shrinkage of the mixed gel during the drying process to cause the collapse of the pores, and obtaining a framework with mainly large pores.
[0041] At the same time, the freeze-dried precursor material is infiltrated with a metal salt solution, and the chelation between sodium alginate and metal ions can be used to fix the metal ions on the surface of the macropores. During the carbonization process, a large amount of gas escapes from the mixed gel of sodium alginate and chitosan, generating channels connecting multiple macropores. At the same time, the gas escapes through the surfaces of the macropores and channels to obtain mesopores distributed on the surfaces of the macropores and channels. The carbonized metal ions are then removed by acid washing, leaving evenly distributed and smaller micropores.
[0042] By controlling the heating rate of the carbonization process and the type of metal salt solution used, the pore structure of the negative electrode active material can be accurately and effectively regulated to obtain a more unobstructed multi-level pore structure that is conducive to the migration of the electrolyte and its electrolyte metal ions, which is beneficial to reducing the ionic conductivity of the negative electrode active material and improving the rate performance.
[0043] At the same time, the chitosan contains nitrogen, which can form a uniform nitrogen doping effect in situ inside the porous carbon material during the carbonization process, effectively improving the electronic conductivity of the negative electrode active material.
[0044] In some embodiments, the “mixing chitosan and sodium alginate to prepare a mixed gel” comprises:
[0045] Chitosan is dispersed at a mass concentration of 0.5% to 3.5% to obtain a first gel solution, sodium alginate is dispersed at a mass concentration of 0.5% to 3.5% to obtain a second gel solution, and the first gel solution and the second gel solution are mixed at a mass ratio of 1: (0.5 to 2) to obtain a mixed gel.
[0046] In the present application, in order to enable chitosan and sodium alginate to be fully mixed, it is further preferred that chitosan and sodium alginate are first dispersed into a first gel solution and a second gel solution respectively, and then the first gel solution and the second gel solution are mixed, so as to ensure that the chitosan gel particles and the sodium alginate gel particles are fully dispersed and mixed, wherein it is further preferred that the mass of chitosan and sodium alginate in the first gel solution or the second gel solution is 0.5% to 3.5%.
[0047] In some embodiments, a pH buffer is added to the first gel solution and the second gel solution, and the pH buffer is selected from acetic acid / sodium acetate solution.
[0048] In some embodiments, the freeze-drying process is performed at a temperature of -10°C to -40°C, and the process time is 24 to 48 hours.
[0049] In some embodiments, the metal salt solution includes Fe 2+ 、Co 2+ 、Ni 2+ 、Zn2+ , Cu 2+ , Ca 2+ or Fe 3+ One or more metal ions.
[0050] In some embodiments, the metal salt in the metal salt solution includes metal ions of one or more of calcium, iron, cobalt, chromium, nickel, and zinc.
[0051] By adjusting the type of the metal salt, in particular, using the metal salt solution, it is beneficial to control the morphology of the formed micropores and increase the specific surface area of the negative electrode active material.
[0052] In some embodiments, the mass concentration of the metal salt in the metal salt solution is 1% to 3%. During the treatment, the freeze-dried precursor material is immersed in the metal salt solution for 8 to 24 hours.
[0053] When the mass concentration of the metal salt in the metal salt solution is within the above range, it is beneficial to form a large number of micropores on the surface of the macropores and channels of the porous carbon material to increase the sites for the deposition and removal of electrolyte metal ions.
[0054] In some embodiments, in the "drying and carbonization treatment", the drying method is freeze drying, the treatment temperature is -10°C to -40°C, the treatment time is 24 to 48 hours, the carbonization temperature is 800 to 1000°C, and the carbonization time is 3 to 5 hours.
[0055] In some embodiments, the carbonization process is performed using a tube furnace.
[0056] In some embodiments, before the pickling operation, the carbonized material is first ground into a granular carbonized material with an average particle size of 3 to 10 μm.
[0057] Specifically, the average particle size of the ground carbonized material may be 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm.
[0058] By controlling the average particle size of the ground carbonized material within the above range, it is beneficial to form a higher porosity between the negative electrode active materials, which is beneficial to improving the infiltration of the electrolyte into the negative electrode active materials.
[0059] In some embodiments, the acid solution used in the pickling operation is hydrochloric acid or sulfuric acid solution.
[0060] In some embodiments, the acid washing operation is followed by water washing and vacuum drying.
[0061] The acid solution remaining on the negative electrode active material is removed by water washing, and the water residue in the negative electrode active material can be avoided by vacuum drying.
[0062] In some embodiments, the vacuum drying process lasts for 24 to 48 hours.
[0063] Another embodiment of the present invention provides a negative electrode active material prepared by the preparation method described above.
[0064] The prepared negative electrode active material is Figure 1 As shown, the negative electrode active material has a multi-level pore structure and a large specific surface area, which is conducive to promoting the infiltration of the electrolyte and the embedding and extraction of electrolyte ions.
[0065] In some embodiments, the negative electrode active material includes a porous carbon material, which includes macropores with a pore size greater than 200 nm, channels with an inner diameter of 20 to 70 nm, mesopores with a pore size of 2 to 50 nm, and micropores with a pore size less than 2 nm. The macropores are distributed inside and on the surface of the porous carbon material, the channels penetrate and connect different macropores, and the mesopores and the micropores are formed on the pore walls of the macropores and the inner walls of the channels.
[0066] A large number of macropores are formed in the porous carbon material, and the macropores are interconnected by channels, wherein the pore size of the macropores is greater than 200nm, and the inner diameter of the channel is 20-70nm. The macropores can store a certain amount of electrolyte, shortening the transmission distance between the internal material and the electrolyte. The channel is responsible for the connection between the macropores, which is conducive to forming a smooth passage between the internal macropores, thereby forming a circulation network in the porous carbon material that is conducive to the shuttle and diffusion of the electrolyte. The porous carbon material is also provided with mesopores and micropores, which can greatly improve the The specific surface area of the porous carbon material is increased, the attachment sites of the electrolyte metal ions are increased, and further, mesopores and micropores with smaller pore sizes are formed on the inner walls of the macropores and the channels, which is beneficial to the full exposure of the mesopores and micropores on the one hand, and on the other hand, due to the small pore depth, it will not have an adverse effect on the diffusion of the electrolyte. Therefore, the negative electrode active material provided by the present invention has a larger electrolyte metal ion attachment site, and also reduces the diffusion resistance of the electrolyte in the negative electrode active material, greatly enhancing the rate performance and material capacity of the negative electrode active material.
[0067] In some embodiments, the porous carbon material may be selected from a graphitized material, a soft carbon material, or a hard carbon material.
[0068] In some embodiments, when the negative electrode active material is used in a lithium ion battery, the porous carbon material is a graphitized material, which is conducive to the insertion and extraction of lithium ions.
[0069] In some embodiments, when the negative electrode active material is applied to a sodium ion battery, the porous carbon material is a hard carbon material.
[0070] Hard carbon materials refer to disordered carbon matrices in which carbon atoms are found primarily in sp2 hybridized states (tripple bonds) in nanoscale polyaromatic domains. The polyaromatic domains are cross-linked using chemical bonds such as C-O-C bonds. Due to the chemical cross-linking between the polyaromatic domains, hard carbon cannot be converted to graphite at high temperatures. Hard carbon has graphite-like properties, which can be seen by the distinct G band (~1600 cm-1) in the Raman spectrum. -1 However, the carbon is not completely graphitic, as evidenced by the distinct D band (~1350 cm -1 ) represented by.
[0071] Since the radius of sodium ions is larger than that of lithium ions, reversible embedding and de-embedding of sodium ions on graphitized materials is difficult. However, the use of hard carbon materials has a larger interlayer gap and can better meet the requirements for reversible embedding and de-embedding of sodium ions.
[0072] In some embodiments, the negative electrode active material is in a particle form, and the average particle size of the negative electrode active material is 3 to 10 μm.
[0073] In some embodiments, the specific surface area of the negative electrode active material is 800 to 2500 m 2 / g.
[0074] Specifically, the specific surface area of the negative electrode active material can be 800m 2 / g、900m 2 / g、1000m 2 / g、1100m 2 / g、1200m 2 / g、1300m 2 / g、1400m 2 / g、1500m 2 / g、1600m 2 / g、1700m 2 / g、1800m 2 / g、1900m 2 / g, 2000m 2 / g, 2100m 2 / g, 2200m 2 / g, 2300m 2 / g, 2400m 2 / g or 2500m 2 / g.
[0075] The specific surface area of the negative electrode active material can be obtained by testing using the gas adsorption BET method.
[0076] In some embodiments, the reversible capacity of the negative electrode active material under 0.1C charge and discharge conditions is 310-400 mAh / g.
[0077] In some embodiments, the porous carbon material is doped with nitrogen, and the nitrogen is distributed inside the porous carbon material.
[0078] By doping the porous carbon material with nitrogen, it is beneficial to improve the electronic conductivity of the porous carbon material and further optimize the rate performance of the negative electrode active material.
[0079] Preferably, the nitrogen element comes from a precursor material of the porous carbon material. The precursor material is carbonized to obtain the porous carbon material. By introducing the nitrogen element into the precursor material, the uniformity of the dispersion of the nitrogen element can be ensured so that it is distributed inside the porous carbon material, thereby effectively reducing the internal resistance of the porous carbon material.
[0080] In some embodiments, based on the total mass of the porous carbon material being 100%, the doping amount of the nitrogen element is 2.6% to 5.2%.
[0081] The nitrogen doping amount of the porous carbon material is related to the nitrogen content of the precursor material before carbonization. When the nitrogen content of the precursor material is higher, the nitrogen content of the obtained porous carbon material is correspondingly increased.
[0082] Another embodiment of the present invention provides a negative electrode sheet, including a negative electrode current collector and a negative electrode material layer covering the negative electrode current collector, wherein the negative electrode material layer includes the negative electrode active material prepared by the preparation method described above or the negative electrode active material described above.
[0083] In some embodiments, the negative electrode material layer further includes a negative electrode binder and a negative electrode conductive agent, and the negative electrode active material, the negative electrode binder and the negative electrode conductive agent are blended to obtain the negative electrode material layer.
[0084] The negative electrode binder includes polyvinylidene fluoride, copolymers of vinylidene fluoride, polytetrafluoroethylene, copolymers of vinylidene fluoride-hexafluoropropylene, copolymers of tetrafluoroethylene-hexafluoropropylene, copolymers of tetrafluoroethylene-perfluoroalkyl vinyl ether, copolymers of ethylene-tetrafluoroethylene, copolymers of vinylidene fluoride-tetrafluoroethylene, copolymers of vinylidene fluoride-trifluoroethylene, copolymers of vinylidene fluoride-trichloroethylene, copolymers of vinylidene fluoride-fluoroethylene, copolymers of vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene, thermoplastic polyimide, thermoplastic resins such as polyethylene and polypropylene; acrylic resin; sodium hydroxymethyl cellulose; and one or more of styrene butadiene rubber.
[0085] The negative electrode conductive agent includes one or more of conductive carbon black, conductive carbon balls, conductive graphite, conductive carbon fibers, carbon nanotubes, graphene or reduced graphene oxide.
[0086] Another embodiment of the present invention provides a secondary battery, comprising the negative electrode sheet as described above.
[0087] In some embodiments, the secondary battery is a lithium ion battery, a sodium ion battery, a potassium ion battery, an aluminum ion battery, or a magnesium ion battery.
[0088] In some embodiments, the secondary battery is a sodium ion battery.
[0089] In some embodiments, the secondary battery further includes a positive electrode and an electrolyte.
[0090] In some embodiments, the positive electrode includes a positive electrode current collector and a positive electrode material layer disposed on the positive electrode current collector, the positive electrode material layer includes a positive electrode active material, and the positive electrode active material includes one or more of metallic sodium, alloy materials, overplated metal oxides, overplated metal sulfides, phosphorus-based materials, phosphate materials, sulfate materials, titanate materials, and Prussian blue materials.
[0091] The present invention is further described below by way of examples.
[0092] Example 1
[0093] This embodiment is used to illustrate the negative electrode active material and the preparation method thereof disclosed in the present invention, and includes the following steps:
[0094] Sodium alginate with a mass concentration of 2% and chitosan gel with a mass concentration of 2% are prepared respectively, and the solvent is acetic acid / sodium acetate buffer. Then the sodium alginate gel is slowly dripped into the stirring chitosan gel and stirred for 12 hours until it is evenly mixed to obtain a mixed gel, wherein the mass ratio of sodium alginate gel to chitosan gel is 1:1; then the mixed gel is poured into a culture dish and transferred to a freeze dryer for drying for 30 hours, and the dried gel is placed in a 2% mass concentration calcium chloride solution for 12 hours, and after freeze drying, it is placed in a tube furnace for carbonization, the heating rate is 15℃ / min, the carbonization temperature is 900℃, and the carbonization time is 3 hours. The carbonized material is ground, washed with hydrochloric acid and deionized water, filtered, and dried to obtain a hard carbon material with hierarchical pores.
[0095] Example 2
[0096] This example is used to illustrate the negative electrode active material and the preparation method thereof disclosed in the present invention, and includes most of the operation steps in Example 1, except that:
[0097] The mass ratio of sodium alginate gel to chitosan gel is 2:1.
[0098] Example 3
[0099] This example is used to illustrate the negative electrode active material and the preparation method thereof disclosed in the present invention, and includes most of the operation steps in Example 1, except that:
[0100] The metal salt solution was replaced by a 2% calcium chloride solution with a 2% nickel oxalate solution.
[0101] Example 4
[0102] This example is used to illustrate the negative electrode active material and the preparation method thereof disclosed in the present invention, and includes most of the operation steps in Example 1, except that:
[0103] The heating rate during the carbonization process was 20 °C / min.
[0104] Example 5
[0105] This example is used to illustrate the negative electrode active material and the preparation method thereof disclosed in the present invention, and includes most of the operation steps in Example 1, except that:
[0106] Sodium alginate with a mass concentration of 0.5% and chitosan gel with a mass concentration of 3.5% were prepared.
[0107] Example 6
[0108] This example is used to illustrate the negative electrode active material and the preparation method thereof disclosed in the present invention, and includes most of the operation steps in Example 1, except that:
[0109] Sodium alginate with a mass concentration of 3.5% and chitosan gel with a mass concentration of 0.5% were prepared.
[0110] Comparative Example 1
[0111] This comparative example is used to compare and illustrate the negative electrode active material and the preparation method thereof disclosed in the present invention, and includes most of the operation steps in Example 1, except that:
[0112] Sodium alginate was not added, and chitosan gel with a mass concentration of 2% was directly prepared.
[0113] Comparative Example 2
[0114] This comparative example is used to compare and illustrate the negative electrode active material and the preparation method thereof disclosed in the present invention, and includes most of the operation steps in Example 1, except that:
[0115] Without adding chitosan, a sodium alginate gel with a mass concentration of 2% was directly prepared.
[0116] Comparative Example 3
[0117] This comparative example is used to compare and illustrate the negative electrode active material and the preparation method thereof disclosed in the present invention, and includes most of the operation steps in Example 1, except that:
[0118] The mixed gel is dried by vacuum drying.
[0119] Comparative Example 4
[0120] This comparative example is used to compare and illustrate the negative electrode active material and the preparation method thereof disclosed in the present invention, and includes most of the operation steps in Example 1, except that:
[0121] The dried gel is not soaked in calcium chloride solution.
[0122] Comparative Example 5
[0123] This comparative example is used to compare and illustrate the negative electrode active material and the preparation method thereof disclosed in the present invention, and includes most of the operation steps in Example 1, except that:
[0124] During the carbonization process, the heating rate was 5 °C / min.
[0125] Comparative Example 6
[0126] This comparative example is used to compare and illustrate the negative electrode active material and the preparation method thereof disclosed in the present invention, and includes most of the operation steps in Example 1, except that:
[0127] A 2% mass concentration potassium chloride solution was used to replace a 2% mass concentration calcium chloride solution.
[0128] Performance Testing
[0129] 1. The particle size of the negative electrode active material prepared above was tested with reference to the standard "GBT24533-2019", the specific surface area of the negative electrode active material prepared above was tested with reference to the standard "GB / T 19587", and the nitrogen content of the negative electrode active material prepared above was tested with reference to the standard "GB / T19587". The test results are filled in Table 1.
[0130] 2. The negative electrode active materials prepared above were ground with carbon black and PVDF in a mass ratio of 8:1:1, mixed evenly, and coated on the surface of copper foil, and then vacuum dried. Metal sodium was used as the counter electrode, and a glass fiber diaphragm was used as the diaphragm. Sodium perchlorate was used as the electrolyte salt of the electrolyte. The button battery was assembled in a glove box. The button battery model was CR2032. The assembled button battery was charged and discharged at a current of 0.1C in the battery test system, and the 0.1C reversible capacity of the battery was recorded. Then, it was charged and discharged at currents of 1C, 2C and 3C, respectively. The battery capacity (1C, 2C, 3C) measured at different rates was divided by the 0.1C reversible capacity to obtain the capacity retention rate at different rates. The test results were filled in Table 1.
[0131] Table 1
[0132]
[0133] It can be seen from the test results of Examples 1 to 4 that the negative electrode active material prepared by the method disclosed in the present invention has a large specific surface area and a high reversible capacity, which means that the negative electrode active material has abundant sodium storage active sites. In addition, the high rate capacity remains at a high level, which means that the multi-level pore structure of the negative electrode active material greatly promotes the transmission of the electrolyte, thereby improving the rate performance of the material.
[0134] The comparison between Example 1 and Comparative Examples 1 and 2 shows that the carbon material prepared by using only chitosan or only sodium alginate cannot obtain a large specific surface area, which leads to a significant impact on the capacity and rate performance, indicating the uniqueness of the sodium alginate and chitosan mixed material in regulating the pore structure.
[0135] The comparison between Example 1 and Comparative Example 3 shows that vacuum drying cannot make the mixed gel of sodium alginate and chitosan obtain a loose and porous framework, so the metal ion solution cannot fully contact the mixed gel when soaked, and the microporous structure cannot be effectively regulated; in addition, the carbonization process will also cause the material to undergo rapid cross-linking, resulting in the material being unable to form a framework rich in macropores. Therefore, its capacity and rate performance are significantly reduced.
[0136] The comparison between Example 1 and Comparative Example 4 shows that, without the immersion of metal ion liquid, the microporous structure of the material cannot be effectively regulated, and without microporous carbon material, the corresponding active sites for sodium ion storage will be lost, and the capacity will be greatly affected.
[0137] The comparison between Example 1 and Comparative Example 5 shows that the heating rate during carbonization is reduced, so that the specific surface area of the material is also greatly affected. This is because the change in the heating rate will lead to the escape rate of the gas generated by pyrolysis. A lower heating rate means that the gas escape rate is slower, and the entire gas escape process can be completed through only a small number of pore channels, resulting in a greater impact on the formation of mesopores and pore channels, which in turn will lead to the inability to fully expose metal ions and the inability to effectively regulate the microporous structure.
[0138] The comparison between Example 1 and Comparative Example 6 shows that potassium ions with a valence of +1 cannot effectively interact with sodium alginate. Potassium ions are only free outside the gel system and cannot be used to form an effective microporous structure, which ultimately leads to a significant impact on the specific surface area and capacity.
[0139] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a negative electrode active material, characterized in that: The steps include: Dispersing chitosan at a mass concentration of 0.5% to 3.5% to obtain a first gel solution, dispersing sodium alginate at a mass concentration of 0.5% to 3.5% to obtain a second gel solution, and mixing the first gel solution and the second gel solution at a mass ratio of 1: (0.5 to 2) to obtain a mixed gel; freeze-drying the mixed gel to obtain a precursor material; The freeze-dried precursor material is infiltrated with a metal salt solution, wherein the metal salt solution is a metal salt solution with a valence greater than or equal to +2, and the metal salt solution includes Fe 2+ 、Co 2+ 、Ni 2+ 、Zn 2+ , Cu 2+ , Ca 2+ or Fe 3+ One or more metal ions; drying and carbonizing, the carbonization heating rate is 10-20°C / min, to obtain a carbonized material; The carbonized material is pickled with an acid solution to remove metal elements to obtain a negative electrode active material.
2. The method for preparing the negative electrode active material according to claim 1, characterized in that: The freeze-drying treatment temperature is -10°C to -40°C, and the treatment time is 24 to 48 hours.
3. The method for preparing the negative electrode active material according to claim 1, characterized in that: The mass concentration of the metal salt in the metal salt solution is 1% to 3%. During the treatment, the freeze-dried precursor material is immersed in the metal salt solution for 8 to 24 hours.
4. The method for preparing the negative electrode active material according to claim 1, characterized in that: In the "drying and carbonization treatment", the drying method is freeze drying, the treatment temperature is -10°C~-40°C, the treatment time is 24~48h, the carbonization temperature is 800~1000°C, and the carbonization time is 3~5h.
5. The method for preparing the negative electrode active material according to claim 1, characterized in that: Before the pickling operation, the carbonized material is ground into granular carbonized material with an average particle size of 3 to 10 μm.
6. The method for preparing the negative electrode active material according to claim 1, characterized in that: After the pickling operation, water washing and vacuum drying are performed.
7. A negative electrode active material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 6.
8. The negative electrode active material according to claim 7, characterized in that The negative electrode active material includes a porous carbon material, which includes macropores with a pore size greater than 200nm, channels with an inner diameter of 20-70nm, mesopores with a pore size of 2-50nm, and micropores with a pore size less than 2nm. The macropores are distributed inside and on the surface of the porous carbon material, the channels penetrate and connect different macropores, and the mesopores and the micropores are formed on the pore walls of the macropores and the inner walls of the channels.
9. The negative electrode active material according to claim 8, characterized in that The porous carbon material is a hard carbon material.
10. The negative electrode active material according to claim 7, characterized in that: The negative electrode active material is in a granular form, and the average particle size of the negative electrode active material is 3-10 μm.
11. The negative electrode active material according to claim 7, characterized in that: The specific surface area of the negative electrode active material is 800-2500 m 2 / g.
12. The negative electrode active material according to claim 7, characterized in that: The reversible capacity of the negative electrode active material under 0.1C charge and discharge conditions is 310-400 mAh / g.
13. The negative electrode active material according to claim 8, characterized in that: The porous carbon material is doped with nitrogen elements, and the nitrogen elements are distributed inside the porous carbon material.
14. The negative electrode active material according to claim 13, characterized in that: Based on the total mass of the porous carbon material being 100%, the doping amount of the nitrogen element is 2.6% to 5.2%.
15. A negative electrode sheet, characterized in that: It comprises a negative electrode current collector and a negative electrode material layer covering the negative electrode current collector, wherein the negative electrode material layer comprises a negative electrode active material prepared by the preparation method according to any one of claims 1 to 6 or a negative electrode active material according to any one of claims 7 to 14.
16. A secondary battery, characterized in that: Comprising the negative electrode sheet as claimed in claim 15.
17. The secondary battery according to claim 16, characterized in that: The secondary battery is a sodium ion battery.
Citation Information
Patent Citations
Sodium alginate / N-succinyl chitosan composite aerogel and preparation method and applications thereof
CN109647295A
Nanometer network structure charcoal material for potassium ion battery and preparation method and application thereof
CN110065934A